Printable Resin Modified by Grafted Silver Nanoparticles for Preparation of Antifouling Microstructures with Antibacterial Effect - Hazem Idriss (MDPI AG, 2021)
The usage of three-dimensional (3D) printed materials in many bioapplications has been one of the fastest-growing sectors in the nanobiomaterial industry in the last couple of years. In this work, we present a chemical approach for grafting silver nanoparticles (AgNPs) into a resin matrix, which is convenient for 3D printing. In this way, the samples can be prepared and are able to release silver ions (Ag+) with excellent antibacterial effect against bacterial strains of E. coli and S. epidermidis. By the proposed process, the AgNPs are perfectly mixed and involved in the polymerization process and their distribution in the matrix is homogenous. It was also demonstrated that this approach does not affect the printing resolution and the resin is therefore suitable for the construction of microstructures enabling controlled silver ion release and antifouling properties. At the same time the physical properties of the material, such as viscosity and elasticity modulus are preserved. The described approach can be used for the fabrication of facile, low-cost 3D printed resin with antifouling-antibacterial properties with the possibility to control the release of Ag+ through microstructuring.